The effect of algal polysaccharides laminarin and fucoidan on colonic pathology, cytokine gene expression and Enterobacteriaceae in a dextran sodium sulfate-challenged porcine model. (28th March 2016) - O'Shea, C. J.; O'Doherty, J. V.; Callanan, J. J.; Doyle, D.; Thornton, K.; Sweeney, T.
Abstract: The algal polysaccharides laminarin (LAM) and fucoidan (FUC) have potent anti-inflammatory activities in the gastrointestinal tract. Our objective was to examine the impact of prior consumption of LAM and/or FUC on pathology and inflammation following a dextran sodium sulfate (DSS) challenge in pigs. Pigs ( n 7/group) were assigned to one of five experimental groups for 56 d. From 49–55 d, distilled water or DSS was administered intragastrically. The experimental groups were: (1) basal diet + distilled water (control); (2) basal diet + DSS (DSS); (3) basal diet + FUC + DSS (FUC + DSS); (4) basal diet + LAM + DSS (LAM + DSS); and (5) basal diet + LAM + FUC + DSS (LAMFUC + DSS). The DSS group had decreased body-weight gain ( P < 0·05) and serum xylose ( P < 0·05), and increased proximal colon pathology score ( P < 0·05), diarrhoeal score ( P < 0·001) and colonic Enterobacteriaceae ( P < 0·05) relative to the control group. The FUC + DSS ( P < 0·01), LAM + DSS ( P < 0·05) and LAMFUC + DSS ( P < 0·05) groups had improved diarrhoeal score, and the LAMFUC + DSS ( P < 0·05) group had improved body weight relative to the DSS group. The FUC + DSS group ( P < 0·001), LAM + DSS group ( P < 0·05) and LAMFUC + DSS group ( P < 0·001) had lower IL-6 mRNA abundance relative to the DSS group. The LAM + DSS group had reduced Enterobacteriaceae in proximal colon digesta relative to the DSS group ( P < 0·05). In conclusion, FUC or a combination of FUC and LAM improved body-weight loss, diarrhoeal scores and clinical variables associated with a DSS challenge in pigs, in tandem with a reduction in colonic IL-6 mRNA abundance.